Artificial Intelligence (AI) Assisted CT/MRI Image Fusion Technique in Preoperative Evaluation of a Pelvic Bone Osteosarcoma - Du, Xin-hui; Wei, Hua; Li, Po; Yao, Wei-Tao (Frontiers in Oncology, 2020)
Surgeries of pelvic bone tumors are very challenging due to the complexity of anatomical structures and the irregular bone shape. CT and MRI are used in clinic for tumor evaluation, each with its own advantages and shortcomings. Combining the data of both CT and MRI images would take advantage of the merits of both images and provide better model for preoperative evaluation. We utilized artificial intelligence (AI) assisted CT/MRI image fusion technique and built a personalized 3-D model for preoperative tumor margin assessment. A young female patient with pelvic osteosarcoma was evaluated with our novel image fusion 3-D model in comparison with 3-D model based solely on CT images. Fusion image model showed more detailed anatomical information and discovered multiple emboli within veins which was previously neglected. The discovery of emboli implied abysmal prognosis and discouraged any attempts for complex reconstruction after tumor resection. Based on the experience with this pelvic osteosarcoma, we believe that our image fusion model can be very informative with bone tumors. Though further validation with large number of clinical cases are required, we propose that our model has the potential to benefit the clinic in the preoperative evaluation of bone tumors.